Overcoming Resistance to Organizational Change: Strong Ties and Affective Cooptation - Battilana, Julie; Casciaro, Tiziana (Management Science, 2013)
We propose a relational theory of how change agents in organizations use the strength of ties in their network to overcome resistance to change. We argue that strong ties to potentially influential organization members who are ambivalent about a change (fence-sitters) provide the change agent with an affective basis to coopt them. This cooptation increases the probability that the organization will adopt the change. By contrast, strong ties to potentially influential organization members who disapprove of a change outright (resistors) are an effective means of affective cooptation only when a change diverges little from institutionalized practices. With more divergent changes, the advantages of strong ties to resistors accruing to the change agent are weaker, and may turn into liabilities that reduce the likelihood of change adoption. Analyses of longitudinal data from 68 multimethod case studies of organizational change initiatives conducted at the National Health Service in the United Kingdom support these predictions and advance a relational view of organizational change in which social networks operate as tools of political influence through affective mechanisms. This paper was accepted by Jesper Sørensen, organizations.